Software tool for analysis of voxel human body models - Šmondrk, Maroš; Babušiak, Branko; Beňová, Mariana; Janoušek, Ladislav (Lékař a technika, 2021)
The paper describes a software tool created to inspect the anatomical structures of any segmented voxel model of the human body for use in numerical analyses of the interaction of non-ionizing electromagnetic radiation with a metallic implant. A voxel model is a three-dimensional representation of the human body model in the form of a numerical array of indices that identify each element as belonging to a particular tissue, organ, or anatomical part. The process of virtual implant placement within these models while maintaining their anatomical limitations is complex and time-consuming. We have created a software tool in the MATLAB environment to simplify and speed up this process. As a representative case, we used the developed tool to identify three implantation sites of pacing electrodes within the cardiovascular system of the available AustinMan and AustinWoman models.
Keywords: Software; digitální technologie; Computer Simulation; software; lidské tělo; kardiovaskulární nemoci; kardiostimulace umělá; počítačová simulace; Models, Anatomic; Cardiovascular Diseases; Cardiac Pacing, Artificial; Biomedical Research; Human Body; Digital Technology; anatomické modely; biomedicínský výzkum